PELATIHAN PEMBUATAN PELEMBUT PAKAIAN DI SEKOLAH - Yuliarty, Popy; Anggraini, Rini; Wijayanti, Atiek Ike (Universitas Mercu Buana, 2022)
The main purpose of washing clothes after wearing them is to clean them of dirt, sweat and dust. Getting laundry that smells nice and soft should be your second priority. With the presence of innovative detergent products designed complete with fragrance ingredients, the goal of cleaning and scenting clothes can be achieved simultaneously. Once washed, clothes become clean and fragrant. With the weather in tropical countries like Indonesia, human needs are growing, namely wanting comfort in clothing, because of that innovation has arisen to make clothes soft and comfortable to wear, namely using fabric softener. This product functions to soften towels, clothes, and others so that when used it doesn't feel rough on the body. It is hoped that the training in making fabric softener will open the minds of teachers so that it can become a provision for them to do entrepreneurship, which if occupied will be able to help family finances as well as for teaching purposes to students to foster creativity in entrepreneurship.